Pemanfaatan Disainary sebagai Learning Tool pada Mahasiswa IPA - Lucky Amatur Rohmani; Anis Zahrotin; Army Al Islami Ali Putra (Universitas Pahlawan Tuanku Tambusai, 2026)
Advances in digital technology require innovation in efficient learning media, especially for Natural Sciences (IPA) learning. One of the challenges faced by science students is their limited understanding of scientific terms, which typically use English and scientific terminology. This community service activity aims to introduce the use of Disainary (Digital Science Dictionary) as a learning tool for science students. The approach implemented included outreach, training, and mentoring in using the Disainary application. The results of the activity showed an increase in students' understanding of scientific terms, increased digital literacy, and enhanced student learning independence. Disainary has proven effective as a digital learning medium that supports independent and contextual learning.